2016
DOI: 10.1002/ejhf.517
|View full text |Cite
|
Sign up to set email alerts
|

The transcardiac gradient of cardio‐microRNAs in the failing heart

Abstract: Aims Differential microRNA expression in peripheral blood has been observed in patients with heart failure, suggesting their value as potential biomarkers and likely contributors to disease mechanisms. In the present study, we aimed to evaluate the transcardiac gradient of 84 cardio‐microRNAs in healthy and failing hearts to determine which microRNAs are released or absorbed by the myocardium in heart failure. Methods and results Eight healthy volunteers and nine patients with congestive heart failure were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
108
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 43 publications
17
108
1
2
Order By: Relevance
“…20 found 3.67 fold of control group in heart failure patients [39] and after glucose fluctuations [40], it is similar in our study (3.386 fold of control), it suggests that let-7e might be an active role in the pathogenesis of heart failure, so the aberrant expression of let-7e might result in congenital heart disease.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…20 found 3.67 fold of control group in heart failure patients [39] and after glucose fluctuations [40], it is similar in our study (3.386 fold of control), it suggests that let-7e might be an active role in the pathogenesis of heart failure, so the aberrant expression of let-7e might result in congenital heart disease.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…PLSR analysis gave quantitative outputs to how likely each microRNA was involved in our response. Certain microRNA’s identified by our anaylsis have been shown to regulate important function like fibrosis (miR-27a and miR-29c 26, 27 ), cardiac hypertrophy (miR-29c 28 , miR-96 29, 30 , miR-182 31, 32 and miR-185 33 ), angiogenesis (miR-27a 34 ), and apoptotsis (miR-138 35, 36 , miR-25 37 ). Although, our model is predictive of microRNA-based mechanism, these targets still need to be validated in the future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, miRNA-155 was not only upregulated but also positively correlated with left ventricular mass index, a prognostic marker in HF patients. Consistent with the above results, Marques et al showed that miRNA-155 was upregulated in HF patients after screening 84 cardio-miRNAs in blood samples from 9 patients with HF and 8 healthy volunteers [40]. …”
Section: Mirna-155 In Hfsupporting
confidence: 54%